(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
The diet of a population of the Spur-thighed tortoise (Testudo graeca whitei), in the Mergueb Nature Reserve in the Algerian steppe, was studied by direct observation. This tortoise population was fed selectively during the month of April when out of 40 different plant species as potential food, only 11 species were consumed. J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(2): 55-60